Determinants of the growth of entrepreneurs in Malaysia / Nooraini Mat Nawi - Mat Nawi, Nooraini (2011)
This paper reports an exploratory study on relationship entrepreneurs’ growth with inflation, unemployment and interest. The objective of the study is to determine the relationship between inflation rate, unemployment rate and interest rate with entrepreneurs’ growth. For this study, the secondary data are used. The data was collected and tested by using regressions analysis. The most significant variable is unemployment. Overall, the researcher concluded that the entire variables model is acceptable and reliable. By conducting this research, researcher hopes that the growth of entrepreneurs in Malaysia will increase time to time because of its contribution in the development of country’s economy